2020
DOI: 10.1155/2020/2074232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoclays on Moisture Susceptibility of SBS‐Modified Asphalt Binder

Abstract: Moisture susceptibility plays an important role in the damage of asphalt pavement. Failure occurs when asphalt is removed from the aggregate particles due to the decreased adhesion between the asphalt and aggregate in comparison with that between water and the aggregate. In recent years, efforts utilizing nanomaterials to improve the diverse properties of asphalt have proven to be effective. In this study, three types of nanoclays were used to modify styrene-butadiene-styrene- (SBS-) modified asphalt. The resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
4
0
1
Order By: Relevance
“…Adding graphene and other materials can improve the bonding performance and other physical properties of asphalt. Some researchers have found that nanocells improved the moisture resistance and bonding strength between the polymer and the modified adhesive system [ 96 ]. The residual bee structure in the nanocell modified asphalt was higher than that in the SBS modified asphalt, indicating that the addition of nanocells made the surface morphology of asphalt more resistant to water damage [ 96 ].…”
Section: Afm Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Adding graphene and other materials can improve the bonding performance and other physical properties of asphalt. Some researchers have found that nanocells improved the moisture resistance and bonding strength between the polymer and the modified adhesive system [ 96 ]. The residual bee structure in the nanocell modified asphalt was higher than that in the SBS modified asphalt, indicating that the addition of nanocells made the surface morphology of asphalt more resistant to water damage [ 96 ].…”
Section: Afm Data Analysismentioning
confidence: 99%
“…Some researchers have found that nanocells improved the moisture resistance and bonding strength between the polymer and the modified adhesive system [ 96 ]. The residual bee structure in the nanocell modified asphalt was higher than that in the SBS modified asphalt, indicating that the addition of nanocells made the surface morphology of asphalt more resistant to water damage [ 96 ]. In addition, the addition of nanocells could also increase the roughness of the SBS modified asphalt.…”
Section: Afm Data Analysismentioning
confidence: 99%
“…Among many modifiers, the styrene butadiene styrene (SBS) is capable of forming a physically cross-linked network structure with asphalt under appropriate conditions. Thus, SBS improves the deformation resistance under high temperatures and cracking resistance at low temperatures, which contributes to its wide application [ 8 ]. However, with the continuous increase in traffic loads and the frequent occurrence of extreme high-temperature climates, research is focused on improving the performance of SBS asphalt.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they are incessantly subjected to the combinations of repetitive loads of vehicles, in the same way the environmental loads that occur over the years of services, causing cracking, furrow formation and damage that is caused by water on the surface of the asphalts. These forms of wear cause degradation in yields and reducing the life cycle of asphalt pavement, causing appreciable economic damage [2].…”
Section: Introductionmentioning
confidence: 99%